Avaliação de danos ambientais: estudo de caso em indústria de agroquímicos - Estivalet, Sandro Delevati (2004)
This work searchs to present and to analyze from data of the research the ambient damages in chemical industry, examining and evaluating the costs and perspective do not incident from the same through otimization technics using tools as Hazop, What-if, Analyze of Risks and Preventive Programs of Security, at last to show all the resources to minimize the risks of environment. The collect of data consists in the investigation, through the job of method system more adquate with the problematic of the research. In this dissertation the method applied was of the research action and was used collection of data was carried through by means of documents analyzes and free observation. The observed impact after the event was that the same could be prevented, if before and during implant of the project of the industrial plant should had better discussion in decision, beside this occurred a great break relationship of the community with the company. The recommendation is to use as lines of direction analyzes environment effective, aiming the best adapt of the enterprise with the economic reality, opting to the preventive attitudes, evaluating all the impacts before any taking of decision. The main prominences in apply of these tools is the prevention and reduction of the risks and accidents, obtention of information that they can subsidize taken of decision managemental, valuation and reduction of the aspects and decurrent environment impacts of the productive process and to get the recognition of external and intern public as environment company responsible.